Sons da contracultura: o rock no Brasil nas décadas de 1960 e 1970 - Saggiorato, Alexandre (2019)
The present study intends to understand and analyze the characteristics of the musical language of the Brazilian rock bands of the 1960s and 1970s, which hypothesized that this movement within a political and social context of the time allowed the conception of an odd sonority, contributed to the formation of a countercultural identity in the country. During this period, rock artists opposed the military regime in a transgressive way involved in the behavioral and musical attitudes of the groups that characterized at that moment an act subversive to censorship and repression. However, the musicians did not allude to the proposals of sectors of resistance to the regime where they sought a politically engaged art that encompassed only one song, according to them, genuinely Brazilian. Another important issue is that the groups were part of the music industry, but in some cases, they were marginalized due to the incorporation of hybrid sound elements such as classical and Brazilian music, making part of the society of the country not understand the rockers' ideals. Artists are present at work are Os Mutantes, Tutti-Frutti, Novos Baianos, O Terço, Módulo 1000, Os Brazões, Brazilian Octopus, Som Imaginário, Sá, Rodrix e Guarabyra, Raul Seixas, Liverpool, Bixo da Seda, A Bolha, Almôndegas, Secos & Molhados, Moto Perpétuo, Rita Lee, Arnaldo Baptista, Ney Matogrosso, Gerson Conrad, A Barca do Sol, Perfume Azul do Sol, Guilherme Arantes, Som Nosso de Cada Dia, Casa das Máquinas, Made in Brazil, Terreno Baldio, Joelho de Porco, Ave Sangria, Cezar de Mercês, O Peso, Recordando o Vale das Maçãs, Vímana, Spin, Veludo e Apokalypsis. For a better understanding of the countercultural sound in Brazil, the methodology of analysis used will be that of musicologist Philip Tagg. The sound analyzed through various rock songs recorded in the period in question, will be contextualized transversally by the concepts of territory and deterritorialization.